2022
DOI: 10.1007/s11302-022-09852-8
|View full text |Cite|
|
Sign up to set email alerts
|

Purinoceptor: a novel target for hypertension

Abstract: Hypertension is the leading cause of morbidity and mortality globally among all cardiovascular diseases. Purinergic signalling plays a crucial role in hypertension through the sympathetic nerve system, neurons in the brain stem, carotid body, endothelium, immune system, renin-angiotensin system, sodium excretion, epithelial sodium channel activity (ENaC), and renal autoregulation. Under hypertension, adenosine triphosphate (ATP) is released as a cotransmitter from the sympathetic nerve. It mediates vascular to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…In keeping with this suggestion, other studies have recently revealed that endothelial P2Y 1 receptors are critical in mediating nitric oxide-dependent vasorelaxation [44] and in processes essential for the regeneration of damaged endothelium [45]. This knowledge has stimulated increased interest in considering the P2Y 1 receptor as a potential therapeutic target in the treatment of hypertension [46].…”
Section: Perspectives and Potential Clinical Significancementioning
confidence: 84%
“…In keeping with this suggestion, other studies have recently revealed that endothelial P2Y 1 receptors are critical in mediating nitric oxide-dependent vasorelaxation [44] and in processes essential for the regeneration of damaged endothelium [45]. This knowledge has stimulated increased interest in considering the P2Y 1 receptor as a potential therapeutic target in the treatment of hypertension [46].…”
Section: Perspectives and Potential Clinical Significancementioning
confidence: 84%
“…Ultrasound and radiofrequency RDN showed remarkable BP lowering in off-medicated uncontrolled hypertension patients by 6.3 and 5 mmHg, respectively 9 , 68 . Purinoceptor-mediated effects and purines such as adenosine tri phosphate (ATP) has been observed to increase BP making it a novel target for hypertension treatment that might have an impact on the regulation patterns 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Since 1972, numerous studies have demonstrated that adenosine triphosphate acts as an extracellular signaling molecule that controls blood pressure. 97 In fact, cells including erythrocytes, ECs, and immune cells can produce nucleotides (adenosine triphosphate, adenosine diphosphate, uridine triphosphate, uridine diphosphate) or nucleosides (adenosine) that bind to purinergic receptors for their biological functions. These purinergic receptors contain 2 subfamilies, namely, P1R and P2R.…”
Section: Role Of Edcfs and Edrfs In Pah Pathologymentioning
confidence: 99%